Supercritical fluid-mediated liposomes containing cyclosporin A for the treatment of dry eye syndrome in a rabbit model: comparative study with the conventional cyclosporin A emulsion - Karn PR (Dove Medical Press, 2014)
Pankaj Ranjan Karn,1 Hyun Do Kim,1,2 Han Kang,1,2 Bo Kyung Sun,1,2 Su-Eon Jin,2 Sung-Joo Hwang1,2 1Yonsei Institute of Pharmaceutical Sciences, 2College of Pharmacy, Yonsei University, Yeonsu-gu, Incheon, Republic of Korea Background: The objective of this study was to compare the efficacy of cyclosporin (CsA)-encapsulated liposomes with the commercially available CsA emulsion (Restasis®) for the treatment of dry eye syndrome in rabbits.Methods: Liposomes containing CsA were prepared by the supercritical fluid (SCF) method consisted of phosphatidylcholine from soybean (SCF-S100) and egg lecithins (SCF-EPCS). An in vitro permeation study was carried out using artificial cellulose membrane in Franz diffusion cells. Dry eye syndrome was induced in male albino rabbits and further subdivided into untreated, Restasis®-treated, EPCS, and S100-treated groups. Tear formation in the dry-eye-induced rabbits was evaluated using the Schirmer tear test. All formulations were also evaluated by ocular irritation tests using the Draize eye and winking methods with the determination of CsA concentration in rabbit tears.Results: After the treatment, the Schirmer tear test value significantly improved in EPCS-treated (P=0.005) and S100-treated (P=0.018) groups compared to the Restasis®-treated group. The AUC0–24 h for rabbit’s tear film after the administration of SCF-S100 was 32.75±9.21 µg·h/mg which was significantly higher than that of 24.59±8.69 µg·h/mg reported with Restasis®. Liposomal CsA formulations used in this study showed lower irritation in rabbit eyes compared with Restasis®.Conclusion: These results demonstrate that the novel SCF-mediated liposomal CsA promises a significant improvement in overcoming the challenges associated with the treatment of dry eyes. Keywords: cyclosporin A, liposomes, supercritical fluid, dry eye syndrome